Modular sulfondiimine and sulfondiimidamide synthesis using stable sulfinylamine reagents - Zhang, Z (2022)
In this thesis, novel methods for the synthesis of sulfondiimines and sulfondiimidamides are described. The use of sulfinylamine linchpins in combination with commercially available organometallic reagents and amines provides access to a broad range of sulfondiimines and sulfondiimidamides.